A Study on Polymeric Fibre Reinforced Stabilized Mud Blocks. Issue 1 (January 2021) - Vignesh, N.P.; Arunachelam, N.; Mahendran, K.; Dinesh Kumar, B.
Abstract: It is a known fact that mud blocks casted out of black cotton soil have poor damage resistance due to clayey, brittle and weak nature of the black cotton soil. In order to improve the strength of the cotton soil based mud blocks, additives such as polypropylene filament, polypropylene flakes and poly styrene fibres have been used in addition to a natural binder namely Terminalia chebula. By varying the percentage of the additives and as also soil, sand and lime various fibre reinforced blocks are made. The as-prepared reinforced mud blocks on analysis were found to possess a maximum strength of 13.75MPa when polypropylene was added as a additive. The study revealed that the addition of polymeric additives with the use of Terminalia chebula resulted in reinforcement of the stabilised mud blocks with enhanced strength and durability.